Character Design for Educational Illustration Books in Knowing Visual Communication Design - Seftina, Diani; Aji, Restu Ismoyo; Nisa , Diana Aqidatun (Universitas Ciputra, 2024)
This research discusses the design of character designs in illustration books getting to know DKV for SMA/MA/SMK teenagers. Teenagers need knowledge and information in making plans for the future, one of which starts with preparing to choose the right major in college. This aims to minimize cases of students feeling like they have entered the wrong major. Apart from that, the existence of the DKV sector is still underestimated by some people due to a lack of knowledge about DKV. The method used in this design is a quantitative descriptive and qualitative descriptive data analysis method through interview data, FGD (Focus Group Discussion), observation, questionnaires, and literature study which culminated in the keyword